Why globally GDP, trade, profits, wages, employment decrease and why poverty increases? - Štrukelj, Peter (Management, 2012)
The purpose of the paper is to propose a scientific explanation of why gdp, trade, profits, wages and employment have been globally decreasing and why poverty has been globally increasing between the 2nd quarter of 2008 and the 3rd quarter of 2009. I explain these facts in a scientific manner, that is, by deriving the present state of the global economy (crisis) from the principles of the present global economy (predominately organized in a capitalistic manner). I therefore prove that the crisis necessarily follows from the way the present global economy functions. I argue that the reason for the crisis is the fundamental contradiction between the purpose of companies (increasing profits) and necessary ways in which companies try to increase profits, and that the consequences of this fundamental contradiction are triggered by a general lack of credits.
Keywords: bruto domači proizvod; ekonomski položaj; makroekonomija; revščina; življenjski standard